2005
DOI: 10.1111/j.1600-051x.2005.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single‐visit full‐mouth ultrasonic debridement versus quadrant‐wise ultrasonic debridement

Abstract: Single-visit full-mouth mechanical debridement may have limited additional benefits over quadrant-wise therapy in the treatment of periodontitis, but can be completed in a shorter time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
216
6
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(242 citation statements)
references
References 60 publications
13
216
6
7
Order By: Relevance
“…The number of analgesics used and the body temperature change was the same in both the groups. 29 The experience of pain in full-mouth groups and quadrant therapy was the same in the Quirynen et al 2000 study after the fi rst day of treatment (half mouth treat ment) but this was signifi cantly higher in full-mouth therapy after the second day (completion of the therapy). The usage of analgesics was higher for full mouth groups after the second day and five patients were reported to have a rise in body temperature to more than 38°C.…”
Section: Patient Complicationsmentioning
confidence: 80%
See 4 more Smart Citations
“…The number of analgesics used and the body temperature change was the same in both the groups. 29 The experience of pain in full-mouth groups and quadrant therapy was the same in the Quirynen et al 2000 study after the fi rst day of treatment (half mouth treat ment) but this was signifi cantly higher in full-mouth therapy after the second day (completion of the therapy). The usage of analgesics was higher for full mouth groups after the second day and five patients were reported to have a rise in body temperature to more than 38°C.…”
Section: Patient Complicationsmentioning
confidence: 80%
“…Koshy et al 2005 showed that the lar results than quadrant therapy. This was 2h 19 min for FMD, 2h 7 min for FRp and 2h 58 min for quadrant scal ing and root planing.…”
Section: Time Spentmentioning
confidence: 97%
See 3 more Smart Citations